(3cJGH GdCZPjIs - (3gHI Gddg Hf RjO Hf MSf Hf GaQGFje Hf jYbhH Hf LejY GdGSQGFjdj, GdeJWHH GdeUQj,J (B594 (3g` s ((3YHO Gddg Hf CMeO s)
(3ChdgG (B:s
(3Gdbhd ai GdHWjN CeG Gdbhd ai GdHWjN ajbSe bSeI MSfI Ydi CQHYI VQhH dCf efgG GdHWjN GdQjai s
(3BNQgG (B:s
(3hYLf HeGA GdJQeS hdWN Hg GdehGTi fLR GdLRA GdKGfi s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B72s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1394s
Keywords: (3GdWHs